Agrarian Revolt in the Sierra of Chihuahua, 1959-1965 - Henson, Elizabeth (Elizabeth Anne) (The University of Arizona Press, 2019)
"Recounts Mexico's pivotal first socialist guerilla struggle in 1965, when armed farmers, agricultural workers, students, and teachers attacked an army base in Chihuahua with deadly consequences"--Provided by publisher.